Nilai-nilai Sosial Kumpulan Cerpen Solopos dan Kelayakannya Sebagai Bahan Ajar dalam Pembelajaran Apresiasi Prosa - Sal Sabila Asmaning Trias, Estri; Zuliyanti (Universitas Muhammadiyah Kotabumi, 2026)
This study is motivated by the importance of utilizing literary works as a learning medium that not only develops students’ literary appreciation skills but also instills social values in them. In the practice of literature education in schools, teaching materials tend to be limited to textbooks, thus failing to present contextual social realities to students. Therefore, this study aims to analyze the social values in the collection of short stories from the January–June 2025 edition of Solopos and their suitability as teaching materials in prose appreciation education. This study employs a qualitative descriptive method using content analysis. Data were collected through literature review, reading, and note-taking of 21 short stories as primary data sources. The research findings reveal 21 diverse categories of social values, including empathy, compassion, solidarity, ethics, loyalty, justice, social inequality, criticism of money politics, and social media ethics. Based on the criteria for selecting teaching materials according to Rahmanto (1988), this collection of short stories is deemed suitable for use in high school literature education. These criteria are met through three main aspects: (1) a communicative language aspect appropriate to students’ reading levels; (2) a psychological aspect relevant to students’ developmental stages; and (3) a sociocultural background aspect that contextually represents societal realities. This study provides a variety of alternative teaching materials to address reliance on textbooks while fostering students’ character and empathy toward the dynamics of community life in the digital age.